THE INFLUENCE OF GOOD CORPORATE GOVERNANCE AND CORPORATE SOCIAL RESPONSIBILITY ON COMPANY VALUE WITH PROFITABILITY AS INTERVENING VARIABLES - Agus Ismaya Hasanudin; Rahma Sukmadianti; Sabaruddinsah (International Journal Labs, 2022)
This study aims to determine the effect of good corporate governance and corporate social responsibility on firm value with profitability as an intervening variable. The sample used in this study is the Manufacturing Company in the Consumer Goods Industry Sector which is listed on the Indonesia Stock Exchange. This study uses secondary data that refers to information that has been collected from existing sources. In the form of company records or documentation, industry analysis by the media, government publications, internet, websites and others. SPSS 20 was used in this study to analyze research consisting of descriptive statistics and hypothesis testing. The results of this study indicate that Good Corporate Governance has an effect on firm value. Meanwhile, Corporate Social Responsibility has no effect on Company Value.